Make Upaya Pemenuhan Kebutuhan Mineral Hewan Ternak Ruminansia melalui Pelatihan Pembuatan Mineral Blok di Desa Girimulyo, Kecamatan Jatipurno, Wonogiri - Pratama, Halim; Maharani, Aliefia; Citra, Citra; Binsanno, Mirza Musyaffa; Arkhami, Fadilah Yudi; Azhari, Trie Anindya; Affandi, Azka Syahfira; Rhandhasmara, Muhammad Azka; Helmi, Alfian (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Minerals are essential micronutrient components for ruminant livestock, as they play a crucial role in improving Average Daily Gain (ADG), feed-to-muscle conversion efficiency, and maintaining physiological functions and the reproductive system. However, at the smallholder farming level, mineral requirements are often neglected due to the limited availability of feed, which typically consists only of grass and straw. Therefore, this training activity aimed to provide education and practical skills to farmers to independently produce mineral blocks as a solution to fulfill the mineral needs of their livestock. The training was conducted five times across several hamlets in Girimulyo Village, Jatipurno Subdistrict, Wonogiri Regency, using the Participatory Rural Appraisal (PRA) method and involving 197 participants. The stages of the activity included material presentation, demonstration, hands-on assistance in production, and distribution of mineral blocks to farmers. The training evaluation employed the AIDA model (Attention, Interest, Desire, Action). This program successfully improved the knowledge, skills, and motivation of the farmers. Participants were able to produce mineral blocks independently and experienced direct benefits for their livestock. Some challenges encountered included material preparation and the drying process of the blocks. The mineral block training proved to be an effective and applicable intervention to improve the quality of smallholder livestock farming. It is recommended that similar training programs be continued with active community involvement, supported by monitoring, evaluation, and publication efforts to ensure program sustainability.